'An Indefatigable Philanthropist': Joseph Tregelles Price (1784–1854) of Neath, Wales. Issue 2 (December 2018) - Allen, Richard C.
Abstract : Joseph Tregelles Price, the Quaker ironmaster of Neath Abbey, Wales (1784–1854), 1 was described by the Cambrian newspaper on his death in December 1854 as 'a leading man of business and an indefatigable philanthropist. His character was one of singular energy, cool discrimination and inflexible integrity'. 2 Moreover, he was the outspoken advocate for the working class 'martyr' Richard Lewis (Dic Penderyn) who was condemned to death for having taken part in the Merthyr Rising of 1831—an event which was part of the drive towards democratic reform in Britain. He was a champion of minority human rights and visualised as a benevolent ironmaster and educationalist in a period of rapid industrial growth as well as social and political discontent in Europe. In this context, this study will consider many of Price's additional humanitarian activities, particularly his advocacy of a peace society (c.1814 onwards) and his stalwart patronage of the anti-slavery movement.